A New Species of the Genus of Alpinia (Alpinia graminifolia D. Fang & G.Y. Lo) Recorded for Vietnam’s Flora - Quoc Trong, Nghiem; Duc Binh, Nguyen; Van On, Tran; Phuong Hanh, Nguyen; Trung Thanh, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 4, 2018)
Abstract: The genus of Alpinia Roxb, with about 250 species worldwide and 35 species in Vietnam, is one of the largest genera of the Zingiberaceae family. Many species of Alpinia , such as Alpinia oblongifolia and Alpinia oxyphylla, are used in Vietnamese traditional medicine. In this research, Alpinia graminifolia , a new species discovered in the mountains of Northern Vietnam (Quang Ninh province and Bac Giang province), was recorded for Vietnam’s flora. The specimens collected in Uong Bi City, Thuong Yen Cong commune, Mount Yen Tu (Quang Ninh province) and Son Dong district, Thanh Luan commune (Bac Giang province), are deposited at Vietnam National Museum of Nature (VNMN), the herbarium of Hanoi University of Pharmacy (HNIP), and the herbarium of the Institute of Ecology and Biological Resources (HN). Keywords :Paddy galangal, smaller galangal, Zingiberaceae. References [1] Kai Larsen, J.M. Lock, H. Maas, P.J.M. Maas (1998), Zingiberaceae, In: K. Kubitzki (eds), The families and genera of vascular plants, Flowering plants, Monocotyledons, Alismatanae and Commelinanae (except Gramineae), Vol. 4: 474 - 495, Springer. [2] Smith R.M. (1990), Alpinia (Zingiberaceae): A proposed new infrageneric classification, Notes from the Royal Botanic Garden Edinburgh, 47(1): 1-175. [3] Wu De-lin, Kai Larsen (2000), Zingiberaceae, In: Wu, Z. Y., P. H. Raven & D. Y. Hong (eds), Flora of China, Vol. 24 (Flagellariaceae through Marantaceae): 322-377, Science Press, Beijing. [4] Phamh. (2000), Illustr. Fl. Vietn.. Publishing house Young, Vol. 3: 432-461. [5] Lê Thị Hương, Trần Thế Bách, Nguyễn Quốc Bình, Lý Ngọc Sâm (2015), New record of Alpinia polyantha D. Fang for flora of Vietnam, J. of Science, VNU, Vol. 31 (4S): 154-157. [6] Lê Thị Hương, Đỗ Ngọc Đài, Nguyễn Quốc Bình, Nguyễn Trung Thành (2017), Alpinia rugosa S. J. Chen & Z.Y Chen (Zingiberaceae), A new record for Flora of Vietnam, J. of Science, VNU, Vol. 33 (1): 101-104. [7] Ngọc Sâm Lý (2017), "Alpinia newmanii sp. nov. (Zingiberaceae) from central Vietnam", Nordic Journal of Botany, 35 (2): 176-181. [8] Fang Ding (1978), "Some new taxa of Zingiberaceae from Kwangsi (2)", Acta Phytotaxonomica Sinica, 16 (4): 77-82.